Associations of melamine and cyanuric acid exposure with markers of kidney function in adults: Results from NHANES 2003–2004. (August 2020) - Guo, Jianqiu; Wu, Chunhua; Zhang, Jiming; Chang, Xiuli; Zhang, Yubin; Cao, Yang; Zhou, Zhijun
Highlights: Melamine was nearly ubiquitous with a geometric mean of 1.38 μg/L in U.S. adults. A novel method for covariate-adjusted creatinine standardization was applied. Individuals with high melamine exposure had lower eGFR than those with low melamine exposure. Abstract: Higher melamine exposure may increase the risk of kidney stone formation and kidney injury in infants, but little is known about the potential nephrotoxic effects of environmental low-dose melamine and its derivative exposure on kidney function of adults in the general population. Our objective was to assess associations between urinary concentrations of melamine and its derivative, cyanuric acid, and kidney function through analyzing the data from the National Health and Nutrition Examination Survey (NHANES) 2003–2004. Information on 298 participants aged ≥20 years was utilized. Urinary melamine and cyanuric acid levels were measured using liquid chromatography-tandem mass spectrometry (LC-MS/MS). Estimated glomerular filtration rate (eGFR) and urinary albumin-to-creatinine ratio (UACR) were calculated to reflect kidney function. Covariate-adjusted creatinine standardization concentrations accounting for sex, race, age, race/ethically, and body mass index, was employed to control potential confounding of kidney function. Multivariable linear regression models were conducted to estimate associations of covariate-adjusted creatinine standardization urinary melamine and cyanuric acid concentrations with eGFR and UACR. Log-binomial regression models were performed to estimate risks of impaired kidney function and hypertension associated with urinary melamine and cyanuric acid levels. The geometric mean values of urinary melamine and cyanuric acid concentrations were 1.51 μg/L [95% confidence interval (CI): 1.21 μg/L, 1.89 μg/L] and 5.86 μg/L (95% CI: 5.34 μg/L, 6.44 μg/L), respectively. The median value of estimated daily intake (EDI) for melamine was 0.06 (ranging from undetectable to 1.11) μg/kg body weight/day calculated by urinary concentration and creatinine excretion accounting for sex and body weight. Adults in the fourth quartile of melamine and cyanuric acid exposure had 0.142 mL/min/1.73 m 2 (95% CI: −0.271, −0.014) and 0.106 mL/min/1.73 m 2 (95% CI: −0.020, 0.006) lower eGFR for melamine and cyanuric acid, respectively, compared to participants in the first quartile of exposure with adjustment for potential confounders. To our best knowledge, this is the first study to report associations between melamine and its derivative and kidney function of the U.S. adults from NHANES 2003–2004. The suggestive evidence revealed that individuals with high melamine exposure had lower eGFR than those with low melamine exposure, although no significant association between melamine and cyanuric acid exposure and markers of kidney function was observed. These findings should be interpreted with caution regarding the possible reverse causality.